Satu Desa, Seribu Hikmah: Catatan Perjalanan KKN di Desa Samangki: One Village, a Thousand Wisdoms: Notes on a KKN Journey in Samangki Village - Khaerul Aqbar; Jamaluddin, Jamaluddin; Azwar, Azwar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The Community Service Program (KKN) is designed to bridge the gap between academic knowledge and the complexities of real-world social dynamics. Through this program, students are not only expected to apply theoretical and scientific concepts but are also trained to adapt, communicate, and collaborate with various segments of society. The primary aim is to enhance students' capacity for learning alongside communities, especially in remote and underdeveloped areas, by applying Islamic knowledge in an integrative manner, as implemented in Samangki Village, Simbang District, Maros Regency. The adopted model is Integrated Community Service, a method that combines academic learning with direct community empowerment practices. The results of the program showed a significant increase in community enthusiasm and participation in various activities, including leading congregational prayers (rawatib and tarawih), delivering religious talks and Ramadan sermons, teaching at children's Qur'anic schools (TKA/TPA), organizing workshops, giving Friday sermons, and conducting social initiatives such as distributing iftar meals and basic food packages, holding children's religious festivals, cupping therapy education, and running short-term Islamic boarding schools (pesantren kilat). All of these programs were successfully implemented and achieved a 100% success rate. The implication of this program is that integrative KKN has proven effective in strengthening the religious and social capacities of the community. Moving forward, program effectiveness can be enhanced through closer collaboration with village authorities, improved infrastructure access, and active support from community leaders.